Protein structure shapes immunodominance in the CD4 T cell response to yellow fever vaccination - Maximilian Koblischke (Nature Portfolio, 2017)
Abstract The live attenuated yellow fever (YF) vaccine is a highly effective human vaccine and induces long-term protective neutralizing antibodies directed against the viral envelope protein E. The generation of such antibodies requires the help of CD4 T cells which recognize peptides derived from proteins in virus particles internalized and processed by E-specific B cells. The CD4 T helper cell response is restricted to few immunodominant epitopes, but the mechanisms of their selection are largely unknown. Here, we report that CD4 T cell responses elicited by the YF-17D vaccine are focused to hotspots of two helices of the viral capsid protein and to exposed strands and loops of E. We found that the locations of immunodominant epitopes within three-dimensional protein structures exhibit a high degree of overlap between YF virus and the structurally homologous flavivirus tick-borne encephalitis virus, although amino acid sequence identity of the epitope regions is only 15–45%. The restriction of epitopes to exposed E protein surfaces and their strikingly similar positioning within proteins of distantly related flaviviruses are consistent with a strong influence of protein structure that shapes CD4 T cell responses and provide leads for a rational design of immunogens for vaccination.